Olympic sport and physical activity promotion: the rise and fall of the London 2012 pre-event mass participation 'legacy'. Issue 4 (1st October 2016) - Bretherton, Paul; Piggin, Joe; Bodet, Guillaume
ABSTRACT: The legacies of Sport Mega Events (SMEs) such as the Olympic Games are increasingly regarded as significant opportunities to increase sport and physical activity (PA) participation. Major sport/PA legacy objectives may even be pursued before the event takes place. This article examines a specific pre-event sport/PA policy target of the London 2012 Olympic Games: the aim of increasing overall participation by two million between June 2008 and the Games in 2012 (a target that was abandoned in 2011). Within a governmentality analytical framework, this research examined how London 2012's pre-event sport/PA participation legacy targets were constructed by organisations responsible for their delivery. Three specific themes are discussed: the inconsistency between how sport/PA participation was constructed in terms of both 'risk' and 'reward' by different organisations; the reliance upon intangible concepts such as 'inspiration' and the status of the Olympic Games to increase participation; and the rationales given for the subsequent abandonment of the pre-event PA participation targets in 2011. The abandonment of the pre-Games participation targets holds two overarching policy implications for future SME host governments and organisers. First, host governments cannot rely on the unique status or 'inspiration' of the Games alone to increase participation and must pursue this more proactively. Second, the ultimate failure of these policies should not be attributed exclusively to their intrinsic limitations, but also to a range of external environmental factors. Pre-event SME legacies must therefore be planned with sufficient awareness of the social and political contexts in which the event takes place.